Management at the enterprise on the basis of ESG principles in the conditions of sanctions pressure - S. A. Bannikov; A. P. Tsypin; P. G. Lakirev (Вестник университета)
Market development trends that occur continuously provoke the emergence of new approaches, concepts and forms of management of business entities. Special attention should be paid to enterprises and small businesses that are the most flexible and adaptive to external and internal development factors, which is especially relevant at present for the ongoing transformational processes of the economy, market and digitalization of society. The purpose of the study is to improve the management system in small businesses through the new digital solutions for automating marketing in modern conditions. The study examined the prerequisites, prospects and practical experience of using digital solutions for automating marketing activities in the management system of small forms of entrepreneurship in Russia. The research methodology is based on scientific methods of cognition: methods of analysis and synthesis, a comparative method, and is also via the mathematical and statistical methods. The possibilities and potential of applying modern digital solutions by Russian small businesses entities in the country considered in the work will be an important direction for the development of entrepreneurship in the context of digital processes for managing the production and economic activities of domestic enterprises and companies.